Imbalance between angiotensin II and angiotensin-(1–7) in human coronary atherosclerosis. (July 2016) - Li, Wenjing; Li, Jifu; Hao, Panpan; Chen, Wenqiang; Meng, Xiao; Li, Hongxuan; Zhang, Yun; Zhang, Cheng; Yang, Jianmin
Objective: Our previous studies found that angiotensin-(1–7) (Ang-(1–7)) is an endogenous counter-factor of angiotensin II (Ang-II). However, the balance between Ang-II and Ang-(1–7) in the development of human coronary atherosclerosis is not determined. Methods and results: The plasma levels of Ang-II and Ang-(1–7) were detected by enzyme-linked immunosorbent assay (ELISA) in 112 patients with known or suspected coronary artery disease (CAD) undergoing coronary angiography. Patients were divided into three groups based on the coronary angiography as follows: (1) normal ( n = 13); (2) noncritical CAD (<50% stenosis, n = 17); and (3) critical CAD (⩾50% stenosis, n = 82). The plasma levels of Ang-II, Ang-(1–7) and the ratio of Ang-II and Ang-(1–7) (Ang-II/Ang-(1–7) were comparable between the normal and noncritical CAD groups. However, Ang-II, Ang-(1–7), and especially Ang-II/Ang-(1–7), were elevated in patients with critical CAD, compared with patients with normal or noncritical CAD. The level of Ang-II/Ang-(1–7) was positively associated with serious coronary stenosis, and correlated with tumor necrosis factor-alpha (TNF-α) level. Conclusion: Both Ang-II and Ang-(1–7) expression are significantly increased in patients with critical CAD. However, increased Ang-II/Ang-(1–7) ratios may lead to Ang-II over-activation and aggravate atherosclerosis progression.